wasH - Azevedo, M. (Open Schools Journal for Open Science, 2020)
In a bathroom, practically everything is contaminated. The simple act of washing your hands after use can prevent contamination and decrease the appearance of some diseases. But there are few people who carry out this simple action. wasH is an awareness campaign designed by students in professional health education aimed not only at the entire school population but also at the entire population of Entroncamento. Some workshops were held and there are already many restaurants and coffee shops participating in the campaign.